위 천공을 유발한 원발 위 미만 대 B세포 림프종 - 김주석; Ju Seok Kim; 류우선; Woo Sun Rou; 안병무; Byung Moo Ahn; 문희석; Hee Seok Moon; 강선형; Sun Hyung Kang; 성재규; Jae Kyu Sung; et al. (The Korean journal of gastroenterology, 2015)
Spontaneous gastric perforation is a rare complication of gastric lymphoma that is potentially life threatening since it can progress to sepsis and multi-organ failure. Morbidity also increases due to prolonged hospitalization and delay in initiating chemotherapy. Therefore prompt diagnosis and appropriate treatment is critical to improve prognosis. A 64-year-old man presented to the emergency department with severe abdominal pain. Chest X-ray showed free air below the right diaphragm. Abdominal CT scan also demonstrated free air in the peritoneal cavity with large wall defect in the lesser curvature of gastric lower body. Therefore, the patient underwent emergency operation and primary closure was done. Pathologic specimen obtained during surgery was compatible to diffuse large B cell lymphoma. Fifteen days after primary closure, the patient received subtotal gastrectomy and chemotherapy was initiated after recovery. Patient is currently being followed-up at outpatient department without any particular complications. Herein, we report a rare case of gastric lymphoma that initially presented as peritonitis because of spontaneous gastric perforation.